Clinical and molecular analysis of a patient with X-chromosome pentasomy (2010)
Introduction: Pentasomy X is a rare chromosomal disorder which affects women. It was first described in 1963 by Kesaree and Wooley. Up to date, less than 30 cases have been reported. We report a case of 28 month old female patient with clinical features of Pentasomy X. Cytogenetic and molecular analysis revealed that her karyotype was 49,XXXXX and that the additional X chromosomes were maternal in origin. Case report: We present a 28 month old female patient with short stature, brachycephaly, characteristic facies, with female external genitalia, hypoplasic labia majora, brachydactyly, bilateral clinodactyly of the fifth finger, dislocation of the right knee with genu varum deformities. Chromosome analysis revealed a karyotype of 49, XXXXX. Materials and methods: We performed DNA extraction and subsequent PCR amplification of 8 microsatellites (STR's) throughout the X chromosome. The amplified products were analyzed in the ALF EXPRESS sequencer. The allelic information obtained was used to construct haplotypes and to analyze gene dosage through the determination of the area under the curve. Results and discussion: Through the analysis of eight STR's in the patient and her parents we were able to determine that the extra X chromosomes were inherited from the mother. We analyze our results and other well documented events that have been related to non-disjunctions. Conclusion: We confirmed through molecular analysis of X-linked DNA markers that the aneuploidy developed from two maternal non-disjunctions.